Respostas

2013-12-15T21:14:10-02:00
 a) f(1) = 2x + 2                                                                                                   2 2 . 1 + 2 =
2 + 2 = 4

b) f(0) = 2x + 2                                                                                                       2 . 0 + 2 =
0 + 2 =
2

c) f (-1) = 2x + 2                                                                                                    
2 (- 1) + 2
- 2 + 2 =
0

d) (1/2) = 2x + 2
2 (1) + 2 =
    2
2  +  2 =
2
1 + 2 =
3